Digital Innovation in Port Service Governance: Implementation of Indonesia Shipping Agencies Association Policy in Southeast Sulawesi - Sarinah Sarinah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2026)
Digital port governance innovation in archipelagic regions frequently faces challenges of institutional fragmentation and infrastructure gaps, meaning performance evaluations must extend beyond narrow economic metrics. This descriptive qualitative study aims to analyze the implementation of the Indonesia Shipping Agencies Association (ISAA) policy in supporting port service digitalization in Southeast Sulawesi, identify policy implementation challenges, and examine the role of digital governance in improving service performance utilizing a Collaborative Digital Port Governance Framework. Data were gathered through in-depth interviews with eleven informants representing service providers, service users, and socio-ecological stakeholders, alongside field observations and document analyses of performance records from 2022–2024. The findings reveal that Inaportnet integration successfully reduced administrative processing times from hours to minutes and drove a 24.5% transaction volume growth by 2024. Crucially, alongside logistical acceleration, digital transparency enhances governance functions and ecological enforcement by mitigating carbon footprints through minimized vessel idling and enabling trace-backed maritime waste monitoring. However, network instability, physical facility constraints, and uneven digital literacy remain primary obstacles in policy implementation. This study recommends integrating real-time carbon footprint tracking modules into the digital platform, enforcing pre-arrival digital logging for ship-generated waste management, and expanding multi-sectoral coordination to include environmental authorities to secure long-term socio-ecological resilience.